2015
DOI: 10.1152/ajpheart.00577.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of homocysteinylation of ACE in endothelial dysfunction of arteries

Abstract: The direct impact of de novo synthesis of homocysteine (Hcy) and its reactive metabolites, Hcy-S-S-Hcy and Hcy thiolactone (HCTL), on vascular function has not been fully elucidated. We hypothesized that Hcy synthesized within endothelial cells affects activity of angiotensin-converting enzyme (ACE) by direct homocysteinylation of its amino-and/or sulfhydryl moieties. This covalent modification enhances ACE reactivity toward angiotensin II (ANG II)-NADPH oxidase-superoxide-dependent endothelial dysfunction. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Our study served to bridge previous laboratory findings [11][12][13][14] with real-world clinical translation. It is the first to demonstrate a positive association between Hcy concentration and SBP or DBP levels at baseline and to elucidate that higher baseline Hcy concentrations, even that of a moderate increase (10-15 μmol/L), are significantly associated with decreased antihypertensive response to short-or long-term enalapril-based antihypertensive treatments in previously untreated hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study served to bridge previous laboratory findings [11][12][13][14] with real-world clinical translation. It is the first to demonstrate a positive association between Hcy concentration and SBP or DBP levels at baseline and to elucidate that higher baseline Hcy concentrations, even that of a moderate increase (10-15 μmol/L), are significantly associated with decreased antihypertensive response to short-or long-term enalapril-based antihypertensive treatments in previously untreated hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, it is possible that during HHcy, reduced H 2 S promotes ACE activity that may lead to the upregulation of angiotensin II. Another study 13 suggested that increased production of endothelial Hcy and its reactive metabolites (Hcy-S-S-Hcy/Hcy-thiolactone) produces N-and S-homocysteinylation of ACE to increase its activity, resulting in the upregulation of the angiotensin II. The exact mechanism by which elevated Hcy reduces enalapril efficacy still needs to be investigated thoroughly before a conclusion can be drawn.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…These results seem consistent with our observations showing the reduction in plasma ADMA concentration as well as Hcy concentration that was linked to an improved endothelium-dependent vascular relaxation after MNA. Interestingly, Huang et al (2015) showed that Hcy synthesized in endothelium (after Met administration) affected activity of ACE by direct homocysteinylation of its amino- and/or sulfhydryl- moieties. This modification enhanced ACE reactivity toward Ang II and consequently led to NADPH oxidase-superoxide-dependent endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%